Post-Exenteration Orbital Wall Reconstruction With Paramedian Forehead Flap - Mior Faiq Mior Abu Tahrin (Emergency Department of Hospital San Pedro (Logroño, Spain), 2019)
Orbital exenteration is a mutilating surgery that involves the total removal of the orbital contents with partial or total excision of the eyelids. It is usually associated with an extremely disfiguring cosmetic outcome which requires some degree of reconstruction before an artificial eye can be placed into the socket. Often times, the orbital cavity needs to be filled with a soft tissue cover especially if the orbital fissures and optic canal is exposed. Free tissue transfer is thought to be the best option in reconstructing complex defect. However, some conditions do not permit a free flap reconstruction to be performed like in a previously irradiated bed as it increases the risk of vascular complications. We present a case of post orbital exenteration who is not suitable for a free flap and wound coverage was done with a paramedian forehead flap as an alternative.